Process application of Subcritical Water Extraction (SWE) for algal bio-products and biofuels production - Thiruvenkadam, S.; Izhar, S.; Yoshida, H.; Danquah, Michael; Harun, R. (Elsevier, 2015)
Algal biomass is appreciated as an essential bioenergy feedstock owing to the rapid growth rate of algal cells and the capacity to harbor substantial quantities of biochemicals via CO2 biosequestration for biofuel production. Amongst the various thermochemical technologies for converting algal biomass to biofuels, Subcritical Water Extraction (SWE) demonstrates significant capacity for generating liquid transportation fuels from algae with minimal environmental impacts. The SWE process expends pressurized water to produce biocrude or bio-oil as well as aqueous, solid, or gaseous by-products. However, the existence of high levels of heteroatoms in biocrude hinders its application in internal combustion engines, and this has triggered studies into parametric characterization of biocrude production from algal biomass. This article comprehensively reviews the process principles, optimal conditions, engineering scale-up and products development to ascertain the viability of an industrial-scale SWE process for biofuel production from algae.